Math, asked by Narendramodi8891, 1 year ago

P(m)=m3+2m2_m+10then p(a)+p(-a)=?

Answers

Answered by manjunpai2000
14

Step-by-step explanation:

P(m) = m^3 + 2m^2 - m + 10

P(a) = a^3 + 2a^2 - a + 10

P(-a) = (-a)^3 + 2(-a)^2 -(-a) + 10

= (-a)^3 + 2a^2 + a + 10

P(a) + P(-a) = 4a^2 + 20

Answered by shaikhfarhan4728
40

Answer:

★ Question★

p [m] = m³+2m³-m+10 then find p [a]+p[-1]=?

--------------------------------------------------

† solution †

p [m] = m³+2m³-m+10

:⟹p[a]=a³+2a^2- a+10

:⟹p[-a]= -a³+2a^2+a+10

:⟹p [a]+[p-1]

:⟹a³+2a^2-a+10-a³+2a^2+a+10

:⟹4a^2+20

--------------------------------------------------

*Answer*

------------------------------------

:⟹ p [a]+[p-1]=4a^2+20 ꪜ

--------------------------------------

Similar questions